2017
DOI: 10.1186/s12913-017-2646-9
|View full text |Cite
|
Sign up to set email alerts
|

Health practitioners’ emotional reactions to caring for hospitalized children in Lomé, Togo: a qualitative study

Abstract: BackgroundHealth practitioners frequently encounter dying, death and suffering. While providing health care can be stressful, the literature on how different health practitioners cope with the emotional challenges associated with their work is sparse. Further, much of this literature is based on studies conducted in high-income countries. In this study, we explored emotional distress and associated coping strategies among health practitioners working in a pediatric oncology department in a large teaching hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
2
3
0
1
Order By: Relevance
“…In this study students expressed anger, anxiety, fear and depression which are likely to be triggered more often during care of dying patients as nurses frequently interact with the patients. Similar to a study done in Togo [15],results from this study highlighted pressure and failure to save the dying patient could have triggered anger, anxiety and emotional distress during physical process of care of dying patients. Studies have shown that interactions with dying patients stimulate negative feelings of anxiety, stress and burnout and perceptions [16].…”
Section: Psychological and Emotional Reactionssupporting
confidence: 77%
“…In this study students expressed anger, anxiety, fear and depression which are likely to be triggered more often during care of dying patients as nurses frequently interact with the patients. Similar to a study done in Togo [15],results from this study highlighted pressure and failure to save the dying patient could have triggered anger, anxiety and emotional distress during physical process of care of dying patients. Studies have shown that interactions with dying patients stimulate negative feelings of anxiety, stress and burnout and perceptions [16].…”
Section: Psychological and Emotional Reactionssupporting
confidence: 77%
“…Although most health care providers experienced high levels of stress, no support systems were provided by the hospitals' administration systems. Health care practitioners in the study of Kpassagou and Soedje reported increased emotional distress due to the lack of training in coping with loss of a life and prolonged patient suffering (Kpassagou and Soedje, 2017). Even in cases where support was provided, only one study concluded that health care providers benefited from it with respect to their stress levels (Chang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, these activities and behaviors are extremely hazardous and may result in adverse outcomes. Unfortunately, these basic and essential elements of coping with the death and dying process are often never discussed with health science students [ 10 ]. Regardless of the instructional methodology, the introduction and development of death and dying education for health science students must be addressed.…”
Section: Discussionmentioning
confidence: 99%